SENSITIVITY ofLEMON (Citrus limon) SOLUTION TOWARD Edwardsiella tarda - Pebri Radayani Saragih; Morina Riauwaty; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Lemon (Citrus limon) is a fruit that can be used as an antimicrobial/antibacterial because it contains secondary metabolites, such as flavonoids, tannins, terpenoid, and asam sitrat. Edwardsiella tardawas pathogenic bacteriathat can cause diseases in cultured fish.This research was conducted from Mei to Juli 2019, at Parasites and Fish Disease Laboratory, Faculty of Fisheries and Marine, University of Riau. The purpose of this study was to get the sensitivity of lemon(Citrus limon) in inhibit he growth ofEdwardsiella tarda, the range of Minimal Inhibitory Concentration (MIC) and the lethal dose (LD50)of lemon (Citrus limon) solution against to (Pangasius hypophthalmus) with length 7-9 cm by immersion for 24 hours. Sensitivity test is using the method of KirbyBauer disk blank 6 mm disc with dose used were 100-0,3% and control Oxytetracyclin. The results showed that the sensitivity of Lemon solution towardsE. tardaat dose 100% with clear zone 14,96 mm and dose 0,3% with clear zone 6,00 mm. At a concentration of 0,5% was determined as the MIC value with a bacterial density 265,33 CFU / mL.Dose LD50 lemon solution against catfish by immersion for 24 hours in 0,49%Keyword :(Citrus limon), Edwardsiella tarda, Sensitivity, Minimum Inhibitory Concentration, LD50